KAJI SIMULASI VARIASI KECEPATAN INLET AIR PADA MICROBUBBLE GENERATOR TIPE ALIRAN SWIRL DENGAN BAFFLE OUTLET - Batubara, Yongki; Surya Rahmany, Rijal; Ivan Wiyarta Cakra Sujana, I Made (Penerbit Lafadz Jaya, 2026)
The need to improve water quality in the aquaculture and wastewater treatment sectors has driven the development of more efficient aeration technologies. Conventional aerators generally produce large bubbles, resulting in relatively short air-water contact times and low oxygen transfer efficiency. Microbubble generators (MBG) are one solution to this problem because they can produce micro-sized bubbles with a large specific surface area and low-rise velocity. Simulations were performed using the computational fluid dynamics (CFD) method with the Eulerian approach and the k–ε standard turbulence model. The water inlet velocity was varied from 11 to 15 m/s, while the air inlet pressure was set at atmospheric pressure. The simulation results showed that the swirl flow pattern inside the chamber was able to significantly reduce the pressure around the gas nozzle tip. Negative pressure began to form at an inlet water velocity of 13 m/s with a minimum pressure value of −14.05 kPa and decreased further to −50.9 kPa at a velocity of 15 m/s. These results indicate that an increase in swirl flow velocity directly affects the MBG's ability to generate negative pressure and automatically suck in air. The findings of this study can be used as a basis for the design and selection of suitable pumps for swirl-type microbubble generator applications.